Introduction to Oxidative Stress in Biomedical and Biological Research - Michael Breitenbach; Peter Eckl (Biomolecules, 2015)
Oxidative stress is now a well-researched area with thousands of new articles appearing every year. We want to give the reader here an overview of the topics in biomedical and basic oxidative stress research which are covered by the authors of this thematic issue. We also want to give the newcomer a short introduction into some of the basic concepts, definitions and analytical procedures used in this field.